CONVERSION OF PINEAPPLE JUICE WASTE INTO LACTIC ACID IN BATCH AND FED – BATCH FERMENTATION SYSTEMS - Abdullah Mochamad Busairi (Reaktor, 2008)
Pineapple juice waste contains valuable components, which are mainly sucrose, glucose, and fructose. Recently, lactic acid has been considered to be an important raw material for the production of biodegradable lactide polymer. The fermentation experiments were carried out in a 3 litres fermentor (Biostat B Model) under anaerobic condition with stirring speed of 50 rpm, temperature at 40oC, and pH of 6.00. Effect of feed concentration on lactic acid production, bacterial growth, substrate utilisation and productivity was studied. The results obtained from fed- batch culture fermentation showed that the maximum lactic acid productivity was 0.44 g/L.h for feed concentration of 90 g/L at 48 hours. Whereas the lactic acid productivity obtained from fed-batch culture was twice and half fold higher than that of batch culture productivity.  Buangan jus nanas mengandung komponen yang berharga terutama sukrosa, glukosa, dan fruktosa. Asam laktat adalah bahan baku yang terbaru dan penting untuk dibuat sebagai polimer laktat yang dapat terdegradasi oleh lingkungan. Percobaan dilakukan pada fermentor 3 liter (Model Biostat B) di bawah kondisi anaerob dengan kecepatan pengadukan 50 rpm, temperatur 40oC, dan pH 6,00. Pengaruh konsentrasi umpan terhadap produksi asam laktat, pertumbuhan mikroba, pengggunaan substrat dan produktivitas telah dipelajari. Hasil yang didapatkan pada fermentasi dengan menggunakan sistem fed-batch menunjukkan bahwa produktivitas asam laktat maksimum adalah 0.44 g/L,jam dengan konsentrasi umpan, 90 g/L pada waktu 48 jam. Bahkan produktivitas asam laktat yang didapat pada kultur fed-batch lebih tinggi 2,5 kali dari pada proses menggunakan sistem batch